Regression Analysis of the Impact of Guangdong Province's Tertiary Industry on Export Trade Based on the Diamond Model. Issue 1 (August 2021) - Peng, Minjing; Liang, Min
Abstract: With the advent of the era of big data, data analysis can objectively explain many events and behaviors with scientific results. China is actively promoting the development of the service industry and opening up to the outside world. Guangdong is the largest foreign trade province. It is of great significance to analyze the impact of the tertiary industry on the export trade by means of data analysis. Based on Michael Porter diamond model, the data of six variables from 2010 to 2019 are selected under the collection of a large number of data, such as the number of employment in the tertiary industry, research and development expenditure. Unit root test and co-integration test are used to analyze.At last, using the method of stepwise regression, the regression equation model of Guangdong Province's export trade volume under the influence of the tertiary industry is established. Through the model, it is concluded that the research expenditures and development level of the tertiary industry can significantly promote the export trade of goods in Guangdong Province, and then improve the competitiveness of export trade. In addition, this paper also stands on the perspective of the tertiary industry, for the development of commodity export trade in Guangdong Province to put forward relevant suggestions.